A listing of CARICOM meetings arranged alphabetically by acronym/abbreviation 2007-2008 (CCS [Georgetown]GY, 2009)
Provides a record of meetings convened by the CARICOM Secretariat during the period 2007-2008. Lists also, meetings which are considered to be of importance to CARICOM..
Keywords: CONFERENCE PAPERS